Can You Count in Greek? : Exploring Ancient Number Systems (Grades 5-8) - Leimbach, Judy (Routledge, 2023)
Discovering the way people in ancient cultures conducted their lives is fascinating for young people, and learning how these people counted and calculated is a part of understanding these cultures. This book offers a concise, but thorough, introduction to ancient number systems. Students won't just learn to count like the ancient Greeks; they'll learn about the number systems of the Mayans, Babylonians, Egyptians, and Romans, as well as learning Hindu-Arabic cultures and quinary and binary systems. Symbols and rules regarding the use of the symbols in each number system are introduced and demonstrated with examples. Activity pages provide problems for the students to apply their understanding of each system. Can You Count in Greek? is a great resource for math, as well as a supplement for social studies units on ancient civilizations. This valuable resource builds understanding of place value, number theory, and reasoning. It includes everything you need to easily incorporate these units in math or social studies classes. Whether you use all of the units or a select few, your students will gain a better understanding and appreciation of our number system.Grades 5-8.